Practices and principles of IT governance in Australian legal aid organizations - Heera, Deepti; Chang, Vanessa (ACIS, 2008)
Information Technology (IT) governance has emerged a a fundamental issue for organizations worldwide as organizations depend on IT. IT governance is an integral part of corporate practice; it consists of leadership and organizational structures, processes and communication systems. The underlying goals for implementing an IT governance framework are to maximize operational effectiveness of business processes; align IT strategies with business strategies and objectives; and conform to regulations. This paper presents a comprehensive and pragmatic model of IT Governance through an integrated framework of structures, processes and communications capabilities. This framework integrates the work of Van Grembergen, De Haes & Guldentops' (2004) IT Governance framework with the principles of IT Governance proposed by Weill and Ross (2004). An amended IT Governance represents one of the major contributions of this paper. The case study presented in the paper investigates the IT governance practices and principles adopted in two Australian legal aid organizations.